Drivers and Barriers for Going Green: Perceptions from the Business Practitioners in Malaysia - S-P Loke; K Khalizani; S Rohati; A Sayaka (ASEAN Journal on Science and Technology for Development, 2014)
The changes of global environmental conditions have placed great challenges to governments and societies. While it is not easy for the companies to go green, we need a renewed concern for our environment in order to revive the nation’s economic growth, social cohesion and ecological balances. This article identifies the drivers and barriers for the business industry to adopt green practices. A total of 571 business companies from the Perak State participated in this study. Four variables: (1) Regulations (?=0.159, p<0.05); (2) Social responsibility (?=0.201, p<0.05); (3) Pro-environmental organizational culture (?=0.389, p<0.01); and (4) Organizational supports (?=0.369, p<0.01) werefound to significantly affect the company’s green initiatives. The results indicated that the main internal barriers were: it lacked of financial resources (66.2%) and skilled staff (63.9%); whereas the main external barriers were: the penalty imposed were not severe enough for making any extra efforts (64.8%) and the penalty was light for violation of environmental regulations (63.2%). This research had implications for the academics, practitioners and policy makers. It provided greater insights into the green practices in Malaysian firms. The research findings also urged the local governments to greatly enhance regulatory scrutiny on the production and manufacturing industries.